2009
DOI: 10.1038/sj.bjc.6605049
|View full text |Cite
|
Sign up to set email alerts
|

Positive lymph node retrieval ratio optimises patient staging in colorectal cancer

Abstract: These guidelines are a statement of evidence and consensus of the authors regarding their views of currently accepted approaches to treatment. Any clinician seeking to apply or consult these guidelines is expected to use independent medical judgment in the context of individual clinical circumstances to determine any patient's care or treatment. The National Comprehensive Cancer Network makes no representations nor warranties of any kind whatsoever regarding their content, use, or application and disclaims any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 162 publications
5
66
0
1
Order By: Relevance
“…For rectal cancer the prognostic significance of the metastatic LNR was earlier addressed in four studies (34)(35)(36)(37). All these studies determined the predictive capacity of LNR in addition to the previous (6 th edition) TNM classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For rectal cancer the prognostic significance of the metastatic LNR was earlier addressed in four studies (34)(35)(36)(37). All these studies determined the predictive capacity of LNR in addition to the previous (6 th edition) TNM classification.…”
Section: Discussionmentioning
confidence: 99%
“…Only in the study by Moug et al (37) neoadjuvant radiotherapy was taken into account and then only in 21 patients. Neo-adjuvant therapy diminishes the number of retrieved lymph nodes (27-29;38).…”
Section: Influence Of Lymph Node Yieldmentioning
confidence: 99%
“…For this reason, lymph node ratio (LNR; number of metastatic LNs/number of harvested LNs) has been studied in colorectal cancer to complement the current staging system for more precise prediction of patient prognosis (Peschaud et al, 2008;Rosenberg et al, 2008;Kim et al, 2009;Moug et al, 2009). These studies have found that, LNR is not only an important prognostic indicator, but also a more accurate stratification system than the current metastatic lymph node number-based staging system in colorectal cancer (Peschaud et al, 2008;Rosenberg et al, 2008;Kim et al, 2009;Moug et al, 2009). Preoperative chemoradiotherapy (CRT) followed by total mesorectal excision (TME) is the current standard of care for patients with T3 or T4 tumors and/or positive lymph nodes (Kapiteijn et al, 2001;Sauer et al, 2004). However, some studies have demonstrated that the number of harvested LNs is significantly decreased in rectal cancer patients received preoperative CRT (Rullier et al, 2008;Doll et al, 2009;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ceelen et al [42], in a systematic review of the prognostic value of the LNR in stage III colorectal cancer, stated that it is a stronger prognostic factor than the number of LN for both colon and rectal cancer patients. All identified studies about rectal cancer [43][44][45][46][47][48][49][50] showed that the LNR is an independent predictor of overall survival and disease-free survival. In particular, Rosenberg et al [46] in 1,263 rectal cancer patients over a 25-year time period and Peschaud et al [47] in 307 patients with high, mid, or low rectal cancer reported LNR as an independent prognostic factor, even when fewer than 12 LN were examined.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Rosenberg et al [46] in 1,263 rectal cancer patients over a 25-year time period and Peschaud et al [47] in 307 patients with high, mid, or low rectal cancer reported LNR as an independent prognostic factor, even when fewer than 12 LN were examined. Nevertheless, several limitations apply to the interpretation of the results of these studies: most did not separately analyze intra-and extraperitoneal rectal cancer patients [43,46,47], and some included only upper rectal cancer patients [50], had a median follow-up period of less than 5 years [45,[47][48][49][50], did not report data regarding the surgical technique used [43,49], or included patients operated on before the introduction of TME [43,46]. Moreover, different cutoff values for LNR were proposed based mainly on quartiles classification rather than a single value.…”
Section: Discussionmentioning
confidence: 99%